IRF6 rs2235375 single nucleotide polymorphism is associated with isolated non-syndromic cleft palate but not with cleft lip with or without palate in South Indian population - Venkatesh Babu Gurramkonda; Altaf Hussain Syed; Jyotsna Murthy; Bhaskar V.K.S. Lakkakula (Brazilian Journal of Otorhinolaryngology, 2018)
Introduction: Transcription factors are very diverse family of proteins involved in activating or repressing the transcription of a gene at a given time. Several studies using animal models demonstrated the role of transcription factor genes in craniofacial development. Objective: We aimed to investigate the association of IRF6 intron-6 polymorphism in the non-syndromic cleft lip with or without palate in a South Indian population. Methods: 173 unrelated nonsyndromic cleft lip with or without cleft palate patients and 176 controls without clefts patients were genotyped for IRF6 rs2235375 variant by allele-specific amplification using the KASPar single nucleotide polymorphism genotyping system. The association between interferon regulatory factor-6 gene intron-6 dbSNP208032210:g.G>C (rs2235375) single nucleotide polymorphism and non-syndromic cleft lip with or without palate risk was investigated by chi-square test. Results: There were significant differences in genotype or allele frequencies of rs2235375 single nucleotide polymorphism between controls and cases with non-syndromic cleft lip with or without palate. IRF6 rs2235375 variant was significantly associated with increased risk of non-syndromic cleft lip with or without palate in co-dominant, dominant (OR: 1.19; 95% CI 1.03–2.51; p = 0.034) and allelic models (OR: 1.40; 95% CI 1.04–1.90; p = 0.028). When subset analysis was applied significantly increased risk was observed in cleft palate only group (OR dominant: 4.33; 95% CI 1.44–12.97; p = 0.005). Conclusion: These results suggest that IRF6 rs2235375 SNP play a major role in the pathogenesis and risk of developing non-syndromic cleft lip with or without palate. Resumo: Introdução: Fatores de transcrição constituem uma família de proteínas muito diversa envolvida na ativação ou repressão da transcrição de um gene, em um determinado momento. Vários estudos usando modelos animais demonstraram o papel dos genes do fator de transcrição no desenvolvimento craniofacial. Objetivo: Nosso objetivo foi investigar a associação do polimorfismo IRF6 intron-6 na fenda labial não sindrômica com ou sem fenda palatina em uma população do sul da Índia. Método: Um total de 173 pacientes com fenda labial não sindrômica com ou sem fenda palatina e 176 controles sem fendas foram genotipados para a variante IRF6 rs2235375 por amplificação alelo-específica utilizando o sistema KASPar de genotipagem de polimorfismo de nucleotídeo único. A associação entre o polimorfismo de nucleotídeo único Fator 6 Regulatório do Interferon(IRF6) intron-6 dbSNP208032210:g.G>C (rs2235375) e o risco de fenda labial não sindrômica com ou sem fenda palatina foi investigado pelo teste qui-quadrado. Resultadoss: Houve diferenças significativas nas frequências de genótipos ou alelos do rs2235375 SNP entre controles e casos com fenda labial não sindrômica com ou sem fenda palatina. A variante IRF6 rs2235375 foi significativamente associada ao aumento do risco de fenda labial não sindrômica com ou sem fenda palatina em modelos codominantes, dominantes (OR: 1,19; IC 95%: 1,03-2,51; p = 0,034) e alélicos (OR: 1,40; IC 95%: 1,04-1,90; p = 0,028). Quando a análise do subgrupo foi realizada, um risco significativamente aumentado foi observado no grupo Fenda Palatina Isolada (OR dominante: 4,33; IC 95%: 1,44-12,97; p = 0,005). Conclusões: Esses resultados sugerem que o polimorfismo de nucleotídeo único IRF6 rs2235375 desempenha um papel importante na patogênese e risco de desenvolvimento de fenda labial não sindrômica com ou sem fenda palatina. Keywords: IRF6, Orofacial clefts, NSCL/P, SNP, Palavras-chave: IRF6, Fendas orofaciais, NSCL/P, SNP